Experimental osteonecrosis: development of a model in rodents administered alendronate - Conte, Nicolau; Spolidorio, Luis Carlos; Andrade, Cleverton Roberto de; Esteves, Jônatas Caldeira; Marcantonio, Elcio (FapUNIFESP (SciELO), 2016)
The main objective of this study was to cause bisphosphonate-related osteonecrosis of the jaws to develop in a rodent model. Adult male Holtzman rats were assigned to one of two experimental groups to receive alendronate (AL; 1 mg/kg/week; n = 6) or saline solution (CTL; n = 6). After 60 days of drug therapy, all animals were subjected to first lower molar extraction, and 28 days later, animals were euthanized. All rats treated with alendronate developed osteonecrosis, presenting as ulcers and necrotic bone, associated with a significant infection process, especially at the inter-alveolar septum area and crestal regions. The degree of vascularization, the levels of C-telopeptide cross-linked collagen type I and bone-specific alkaline phosphatase, as well as the bone volume were significantly reduced in these animals. Furthermore, on radiographic analysis, animals treated with alendronate presented evident sclerosis of the lamina dura of the lower first molar alveolar socket associated with decreased radiographic density in this area. These findings indicate that the protocol developed in the present study opens new perspectives and could be a good starting model for future property design.